The Role of Islamic Religious Education Curriculum in Building Religious Tolerance in the School Environment - Annur Muharridha; Juliani; Siti Selvira; Kanaya Maisa Mulia; Nurul Husna Hasibuan (Yayasan Zia Salsabila, 2025)
Islamic Religious Education (PAI) plays a strategic role in fostering religious tolerance in multicultural school environments. This study aims to analyze the role of the PAI curriculum in instilling tolerance values and exploring the methods and approaches used in teaching. A qualitative approach with a case study design was applied in a secondary school with religious diversity. The findings indicate that the PAI curriculum supports the development of tolerance attitudes through the integration of universal values, such as respect for differences, empathy, and cooperation, into the teaching materials. Dialogical approaches and interaction-based experiential learning proved effective in enhancing students' understanding of diversity. However, challenges such as insufficient teacher training in managing tolerance-based curricula and resistance from some students toward interfaith discussions remain. The PAI curriculum can effectively build religious tolerance in schools if supported by adequate teacher training, relevant teaching modules, and synergy among teachers, students, and parents. Recommendations include developing intensive training programs and enhancing the curriculum with a focus on tolerance values.